Ultra-fine grained EUROFER97 steel for nuclear fusion applications - Giulia Stornelli; Andrea Di Schino; Roberto Montanari; Mirko Sgambetterra; Claudio Testani; Alessandra Varone (Journal of Materials Research and Technology, 2024)
EUROFER97 is the european Reduced Activation Ferritic-Martensitic (RAFM) steel, candidate to be used as a structural material in fusion energy systems. One of its operational limits is due to the excessive ductility loss following neutron irradiation below 350 °C. To overcome this drawback, a Thermo-Mechanical Treatment (TMT) has been developed for improving mechanical properties through microstructure refinement without ductility loss. It consists in cold rolling followed by heat treatment of EUROFER97 steel plates preliminary subjected to the standard process. The combination of five cold rolling (CR) ratios (20 %, 40 %, 50 %, 60 %, 80 %) and eight treatment temperatures in the range 400–750 °C (steps of 50 °C) with a soaking time of 1 h has been considered. The samples were investigated through microstructural examinations and mechanical tests (hardness and tensile tests). After heat treatments, recrystallization takes place for each CR ratio with different kinetics depending on both treatment temperature and CR ratio. The results show that the TMT corresponding to cold rolling with CR of 80 % and treatment at 650 °C leads to a remarkable improvement of mechanical properties: in comparison to standard EUROFER97 Yield Stress (YS) increases of ∼18 %, Ultimate Tensile Strength (UTS) of ∼5 % while the uniform elongation (AU) is more than double. The excellent characteristics, promising for nuclear fusion applications, are related to the ultra-fine size of grains, their equiaxed shape, the prevalence of High Angle Grain Boundaries (HAGBs) and the fine dispersion of carbides.